THE MEASUREMENT OF ENVIRONMENTAL RADIATION EXPOSURE AROUND THE LINAC RADIOTHERAPY BUNKER - Kurniasari, Septiana; Hentihu, Fatimah K; Anto, Alfian K; Prasetyo, Henry (Indonesian Physical Review, 2022)
Radiotherapy is cancer therapy using radiation. One of the tools used for radiotherapy is the Linac. Using Linac also can have a detrimental effect on radiation workers, patients, and the public. The reaction can cause activation around the room to become radioactive. Therefore, radiation protection is needed. This research aimed to measure environmental radiation exposure as a radiation protection effort around the Linac bunker. This research uses a quantitative method by collecting data directly on the area around the Linac bunker, with a distance of ± 30 cm from the bunker wall, using the STEP OD-02 Detector. The average Linac operation is 2000 hours/year, while the safe dose limit used is 1/2 dose Limit from Nuclear Power Monitoring Agency. Based on measurements of environmental radiation exposure, there are eight areas classified as safe and four other regions experiencing radiation leakage, including Doors with a radiation exposure difference of 0.078 Sv/hour; West Field (0.074 Sv/hour); TPS Room (0.302 Sv/hour); and Meeting Rooms (0.199 Sv/hour), but still within the safe limit of radiation dose. The environmental radiation exposure around the Linac Radiotherapy bunker is safe.